Software Product Line Configurations Generation using Different Types of Tools – A Comparison - Saini, A; Rajkumar; Kumar, S (International Journal of Computer Sciences and Engineering, 2025)
Feature model's analysis is a booming area and should be automated is a thriving research topic, an area of attraction for both practitioners and researchers from last two decades. Meanwhile, a number of methods and tools facilitate to increase the analysis of feature models and also check complexity of feature model. As numerous of tools are given by researchers and practitioners, but why a tool is used and for which purpose, it's a basic problem and creates a blurry scenario and this blurriness generate hurdles to select an analyzing tool to analyze a feature model. To clear this picture, we present a paper, where we compare four analysis tools (FeatureIDE, SPLOT, FaMa and BeTTy) on the basis of some fundamental factors (Availability of Tool, Cross Tree Constraint, Support Testing, Fault Detection, Product Generation, Statistics of Model and Model Composer). The comparison will show in form of a table at the end of this paper, through which users can choose a tool for their work.